О РЕГИОНАЛЬНОМ КОМПОНЕНТЕ В ОБРАЗОВАТЕЛЬНОЙ ТЕХНОЛОГИИ (Philological Studies, 2019)
The inclusion into educational programes of study of local lore promoted development of questions on regional components of language in theory and methodical aspects. The given clause describing lokalism in literary speech of the townspeople, presented in student’s book by E.V. Erofeeva, T.I. Erofeeva, F.L. Skitova devoted to it (Perm, 2002).